The Influence of Subject Teachers’ Expectations on Junior High School Students’ Learning Motivation: Taking English as an Example - He, Nan (Transactions on Social Science, Education and Humanities Research, 2024)
The relationship between teachers’ expectations and students’ learning motivation is one of the important topics in the field of educational psychology nowadays, and it is also one of the issues that the pedagogical community is concerned about. However, in today’s society, there are still some research gaps in the influence of teachers’ expectations on students’ learning motivation and the internal relationship between them. Therefore, this study takes junior high school students in a middle school in Meizhou, Guangdong Province as the research object, collects the scale data of specific English teachers’ expectations and students’ learning motivation perceived by students, and carries out correlation analysis and regression analysis between the two according to the data. According to the correlation analysis of this study, there is no significant correlation between teachers’ expectations and the undermotivation dimension of learning motivation, but there is a significant correlation with the three dimensions of over-motivation, learning interest, and learning objectives. It shows that positive teachers’ expectations have a significant positive impact on all dimensions of students’ learning motivation. Therefore, the study puts forward the following three suggestions. Firstly, teachers need to give reasonable expectations to students. Secondly, teachers should learn how to guide students’ learning motivation effectively. Last, the study also discusses about teachers’ expectations and learning motivation have a main and extremely important influence on students’ learning performance.